Ejemplo n.º 1
0
 def test_four(self):
     a = predicats.gt(0)
     b = predicats.lt(-5)
     c = predicats.for_all(a, b)
     assert c(-3) is False
Ejemplo n.º 2
0
 def test_two(self):
     a = predicats.gt(0)
     b = predicats.lt(5)
     c = predicats.for_all(a, b, a)
     assert c(10) is False
Ejemplo n.º 3
0
 def test_three(self):
     a = predicats.gt(0)
     b = predicats.lt(5)
     c = predicats.for_all(a, b)
     assert c(-3) is False
Ejemplo n.º 4
0
 def test_two(self):
     a = predicats.lt(0)
     assert a(10) is False
Ejemplo n.º 5
0
 def test_one(self):
     a = predicats.gt(0)
     b = predicats.lt(5)
     c = predicats.for_all(a, b)
     assert c(3) is True
Ejemplo n.º 6
0
 def test_two(self):
     a = predicats.gt(0)
     b = predicats.lt(5)
     c = predicats.for_any(a, b, a)
     assert c(10) is True
Ejemplo n.º 7
0
 def test_four(self):
     a = predicats.gt(0)
     b = predicats.lt(5)
     c = predicats.for_any(a, b)
     assert c(-10) is True
Ejemplo n.º 8
0
 def test_four(self):
     a = predicats.gt(0)
     b = predicats.lt(-5)
     c = a >> b
     assert c(-2) is True
Ejemplo n.º 9
0
 def test_three(self):
     a = predicats.gt(0)
     b = predicats.lt(5)
     c = a >> b
     assert c(-10) is True
Ejemplo n.º 10
0
 def test_two(self):
     a = predicats.gt(0)
     b = predicats.lt(5)
     c = a >> b
     assert c(3) is True
Ejemplo n.º 11
0
 def test_one(self):
     a = predicats.lt(0)
     assert a(-10) is True
Ejemplo n.º 12
0
 def test_one(self):
     a = predicats.gt(0)
     b = predicats.lt(5)
     c = a >> b
     assert c(10) is False